Utilization of Lime Peel Extract as a Preservative for Fresh Mackerel Scad with Different Time and Concentration - Hasmini, Hasmini; Subariyanto, Subariyanto; Patang, Patang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to determine the effect of using lime peel extract as a natural preservative on the shelf life of mackerel scad. The research method used was a Completely Randomized Design (CRD) with four concentration treatments: 0%, 0,5%, 1%, and 1,5% of lime peel extract. The mackerel scad was soaked in the extract for 30 minutes, then stored at room temperature for 0, 6, 12, and 18 hours. The results showed that the addition of 1,5% lime peel extract had the most significant effect in extending the shelf life of the mackerel scad. The chemical test results indicated that fresh mackerel scad soaked in 1,5% lime peel extract and stored for 18 hours had a pH of 3,36. The microbiological test results showed a total bacterial colony count of 5,3 log CFU/g and a total proteolytic bacteria count of 4,6 log CFU/g.